Platelet hyperaggregability in high-fat fed rats: A role for intraplatelet reactive-oxygen species production - Monteiro, Priscila F.; Morganti, Rafael P.; Delbin, Maria A. [UNESP]; Calixto, Marina C.; Lopes-Pires, Maria E.; Marcondes, Sisi; Zanesco, Angelina [UNESP]; Antunes, Edson (Biomed Central Ltd., 2012)
c Background: Adiposity greatly increases the risk of atherothrombotic events, a pathological condition where a chronic state of oxidative stress is reported to play a major role. This study aimed to investigate the involvement of (NO)-soluble guanylyl cyclase (sGC) signaling pathway in the platelet dysfunction from high fat-fed (HFF) rats.Methods: Male Wistar rats were fed for 10 weeks with standard chow (SCD) or high-fat diet (HFD). ADP (10 mu M)-and thrombin (100 mU/ml)-induced washed platelet aggregation were evaluated. Measurement of intracellular levels of ROS levels was carried out using flow cytometry. Cyclic GMP levels were evaluated using ELISA kits.Results: High-fat fed rats exhibited significant increases in body weight, epididymal fat, fasting glucose levels and glucose intolerance compared with SCD group. Platelet aggregation induced by ADP (n = 8) and thrombin from HFD rats (n = 8) were significantly greater (P < 0.05) compared with SCD group. Platelet activation with ADP increased by 54% the intraplatelet ROS production in HFD group, as measured by flow cytometry (n = 6). N-acetylcysteine (NAC; 1 mM) and PEG-catalase (1000 U/ml) fully prevented the increased ROS production and platelet hyperaggregability in HFD group. The NO donors sodium nitroprusside (SNP; 10 mu M) and SNAP (10 mu M), as well as the NO-independent soluble guanylyl cyclase stimulator BAY 41-2272 (10 mu M) inhibited the platelet aggregation in HFD group with lower efficacy (P < 0.05) compared with SCD group. The cGMP levels in response to these agents were also markedly lower in HFD group (P < 0.05). The prostacyclin analogue iloprost (1 mu M) reduced platelet aggregation in HFD and SCD rats in a similar fashion (n = 4).Conclusions: Metabolic abnormalities as consequence of HFD cause platelet hyperaggregability involving enhanced intraplatelet ROS production and decreased NO bioavailability that appear to be accompanied by potential defects in the prosthetic haem group of soluble guanylyl cyclase.
Keywords: Platelet aggregation; Obesity; Reactive-oxygen species; Nitric oxide; Cyclic GMP; BAY 41-2272